PENGARUH PENDALAMAN FINANSIAL DAN KETERBUKAAN PERDAGANGAN TERHADAP PERTUMBUHAN EKONOMI PROVINSI BALI - Sanjaya, Made Wika; Sudirman, I Wayan; Budiasa, I Gede Sudjana (Buletin Studi Ekonomi; VOL.22.NO.1. FEBRUARI 2017 (PP 1-112), 2017)
Economic growth is accompanied by support for the stability of the domestic economy is a target to be achieved by each country. To determine the interest rate policy is a form of financial repression which will impact on the deepening financial and trade openness as drivers of economic growth. This study aimed to determine the effect of financial deepening and trade openness on economic growth in Province of Bali. The results showed that the real interest rate is only positive and significant impact on the deepening of the savings in the short term and long term, but no significant effect on the deepening of credit and trade openness. Further deepening of credit and trade openness positive and significant impact on economic growth of Bali Province in the short term and long term, but deepening of deposits did not significantly affect the economic growth of the province of Bali.